Docking molecular aplicado ao estudo da formação de complexos entre análogos de resveratrol e derivados de 1,2,3-triazol e a enzima COX-2 - Castilho, Luis Nelson Prado (Universidade Federal de São Carlos, 2011)
Prostaglandin H synthases (PGHS), or cyclooxygenases (COX), are known to exist in at least two isoforms, COX-1 and COX-2, encoded by different genes. COX s play a central role in the inflammatory cascade by converting arachidonic acid, released from membrane phospholipids, into bioactive prostanoids. Non-steriodal anti-inflammatory drugs (NSAIDs) represent an important therapeutic category related to the reduction of inflammation, pain and fever, however, can cause gastric and kidney failure. Selective inhibition of COX-2 by NSAIDs known as coxibs leads to a significant reduction of these side effects in addition reduce fatal thrombotic events and act in controlling some types of cancer and progression of Alzheimer's disease, when used for a long period. This study, based on molecular docking, describes the search for the most favorable poses in the formation of complexes between COX-2 and resveratrol analogues and 1,2,3-triazole derivatives. The three dimensional structure of the enzyme, 1cx2, was obtained from the Protein Data Bank (PDB). The structures of the ligands were obtained by molecular modeling. The docking calculations were carried out with the program GOLD 4.1.2. Analyses of the docking results show that interactions with residues of the side pocket of COX are important for the stabilization of the complexes, in particular His90, Arg120, Ser353, Tyr355 and Arg513 should be mentioned. The ligands studied locate, preferably, between α-helices 13 and 26 of the isoenzyme, and the interaction with the serine 353 residue seems to be related to the activity presented by ligands with low IC50 values, a characteristics that can be exploited in rational design of new leader molecules or in the optimization of selective ligands that should occupy the side pocket of the cyclooxygenase active site of COX-2.
Molecular docking applied to the study of complexes formation between resveratrol analogues and 1,2,3-triazole derivatives and the COX-2 enzyme
Keywords: Biotecnologia; Docking; Ciclooxigenase (COX-2); Drogas antiinflamatórias não esteróides (AINEs); Resveratrol; Triazol; PGHS; PGHS; COX; Docking; NSAID; Resveratrol; CIENCIAS EXATAS E DA TERRA::QUIMICA